A novel technique to discriminate inrush and fault in a single-phase transformer. (16th August 2010) - Paraskar, S.R.; Beg, M.A.; Dhole, G.M.; Khedkar, M.K.
This paper presents an algorithm based on a combination of Discrete Wavelet Transforms (DWTs) and Feed-Forward Artificial Neural Network (FFANN) to discriminate magnetising inrush from interturn fault. Interturn faults are staged on custom-built transformer. DWT is used for feature extraction from the differential current during magnetising inrush and interturn faults and FFANN is used to discriminate magnetising inrush from interturn fault. An online algorithm is tested successfully on the custom-built transformer. It is found that the proposed method gives satisfactory results, and may be useful in the development of modern differential relay for transformer protection scheme.